Digital Nomad:Analysis of Legal Impact and Government Influence on The Concept of Cultural Tourism in Bali - Putu Lantika Oka Permadhi; Kadek Apriliani (Journal Equity of Law and Governance, 2024)
Digital nomadism has emerged as a growing trend within the global tourism landscape, offering unique opportunities for Bali’s cultural tourism sector. By attracting remote workers who seek immersive travel experiences, Bali can develop cultural tourism rooted in local wisdom, thus revitalizing its tourism industry. This approach is particularly relevant as the sector recovers from the severe impacts of the Covid-19 pandemic. However, technological advancements have provided support to the tourism and creative economy sectors in navigating the pandemic. The purpose of this research is to understand the legal impacts and government influences on the concept of cultural tourism in Bali. This study employs normative legal research based on secondary data. The research focuses on analyzing legal standards to provide fresh claims, hypotheses, or ideas as guidelines for addressing issues, making it a more in-depth study. The findings indicate that the presence of digital nomads in Bali significantly impacts the preservation of cultural tourism centered on tradition and local wisdom. While this phenomenon brings positive economic effects, such as increased consumption and local investment, the negative impacts on culture and the environment must also be considered. The commercialization of culture, changes in social landscapes, value conflicts, and environmental pressures are the main challenges for Bali in maintaining its cultural identity.